Human resources development innovations in Sumedang district organization section regional secretariat - Vebrianie Aqila Muthia Zahra; Shinta Puspitasari; Rizky Ilhami (Sean Institute, 2024)
This study aims to explain innovation in human resource (HR) development in the organization. Through qualitative data collection and literature study, this research identifies several innovations that can be applied in the context of HR development. This research highlights the importance of innovation in HR development in response to the dynamics that occur within organizations. In an era of globalization and rapid technological development, organizations need to adopt innovative approaches to improve employee competencies and skills. The object of this research was taken located at the Regional Secretariat of the Sumedang Regency Organization Section. This research obtains data and information on how human resource development innovations in the Regional Secretariat of the Sumedang Regency Organization Section have been carried out optimally or not. As well as what factors affect the development of human resources. The report uses a descriptive research analysis approach. The results showed that the Regional Secretariat of the Sumedang Regency Organization Section had carried out optimal human resource development. External factors, namely government policies, cause problems in this human resource development effort. However, employees try to comply with policies because government policies help them develop as human resources. This research found that the Regional Secretariat of the Sumedang Regency Organization Section innovates in human resource development, as well as any factors that can affect HR development efforts that have been or will be carried out by the Sumedang Regency Regional Secretariat. The advice that researchers can give to the Regional Secretariat of the Sumedang Regency Organization Section in innovating human resource development is that they must continue to develop their resources, especially human resources, which are the most important assets.